Examining the Control-Value Theory in the Field of Mathematics Academic Boredom in First-year High school Students - Fereshteh Salemi; Farzaneh Michaeli Manee; Ali Esazadegan (مطالعات روانشناسی تربیتی)
Value-control theory has been used in recent years to predict academic emotions. However, academic boredom as one of the negative emotions has been less investigated. Therefore, the aim of the current research was to test the validity of the value-control theory in predicting academic boredom in the mathematics course of first year high school students. The method of this research was descriptive (causal modeling). The statistical population included all the first tuberculosis students of the second year of secondary school in Urmia city, of which 384 people were selected as a statistical sample using a multi-stage cluster random method. Data were collected using the questionnaires of academic boredom by Acee et al. (2010), academic control by Perry et al. (2001), academic motivation by Vallerand et al. (1992), educational value, academic self-efficacy by Owen and Fronman (1998), and self-regulated learning by Pintrich & De Groot (1990). SPSS23 and Amos26 software were used for data analysis. Data analysis was done using Pearson correlation and structural equations. The findings showed that the components of control-value theory have a significant negative relationship with academic boredom. Based on structural model fit indices, value-control theory was a valid model to explain academic boredom in mathematics. Therefore, it is suggested that those involved in the field of education should inform teachers and students about the components of value-control theory as effective factors in the process of classroom education, so that the probability of academic boredom will decrease.